NUMERICAL STUDY OF THE DESIGN OF THE RECLINING HANDLE FOR THE TOYOTA KIJANG CAPSULE MADE FROM COMPOSITE MATERIAL REINFORCED WITH SUGARCANE BAGASSE FIBERS - Faizin, Kholis Nur; Gascoin, Nicolas; Sumiaji, Sumiaji; Majedi, Farid; Bowo, Prayogo Arie; Aziz, M. Shafwallah Al. (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Rapid advancements in science and technology have increased the demand for renewable and high-performance composite materials. Sugarcane bagasse, an agricultural waste, has potential as a natural fiber reinforcement in composite materials. This study investigates the use of sugarcane bagasse fibers with epoxy and polyester resin matrices for manufacturing the handle reclining component of the Toyota Kijang Kapsul. Molds were successfully fabricated using Silicon Rubber RTV-52 with a catalyst ratio of 1:25, producing precise molds suitable for composite fabrication. Compression testing revealed that epoxy-based composites achieved an average maximum compressive load of 10,673.49 N, approximately 28% higher than polyester-based composites, which averaged 8,332.83 N. Epoxy composites also showed more consistent performance across specimens. Structural analysis using ANSYS indicated that composite handles exhibited lower deformation, higher equivalent stress, and greater safety factors d to plastic counterparts. The handle reclining parts produced from epoxy resin and sugarcane bagasse fibers with a 25:75 fiber-to-resin ratio successfully replicated the original part's appearance and demonstrated superior mechanical performance. This study contributes to the development of cost-effective, environmentally friendly composite materials with practical applications in the automotive industry.